Peran Komunikasi Pemasaran Modern pada Produk Kuliner Tradisional di Teras Jahe Yogyakarta - Dyaloka, Dyaloka Puspita Ningrum; Syakdiah , Syakdiah (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
One business that is still consistently increasing and contributing to the national economy is the growth of the culinary/food and beverage (F&B) business industry, as gastronomic trends continue to be initiated as a new tourism alternative. This research aims to analyze the sales efforts of traditional culinary products carried out by Teras Jahe Yogyakarta using the 10P Marketing Mix theory based on Kotler and Armstrong's perspective. This research uses a qualitative descriptive method through data collection techniques: observation, in-depth interviews, documentation, and literature study. The results of the research show that the management at Teras Jahe Yogyakarta has carried out various promotions in conventional marketing media to digital marketing media, especially those that focus on strengthening the brand image with the tagline